Pengaruh Rasio Keuangan, Pertumbuhan Laba Terhadap Harga Saham LQ-45 Indonesia - Anugraha, Aulya (Politeknik Ganesha Medan, 2024)
This research aims to find empirical evidence of the influence of several financial ratios, namely Current Ratio, Return on Assets, Earnings Per Share, Debt to Equity Ratio, and Total Assets Turnover, as well as profit growth on the stock prices of companies listed in the LQ-45 index on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The method used is quantitative causality with data analysis using multiple linear regression with the Stata application. The research sample was obtained from the OSIRIS database and selected using a purposive sampling method with the following criteria: (1) companies that are consistently listed in the LQ-45 index on the Indonesia Stock Exchange for the 2018-2022 period; (2) companies that issue financial reports in the 2018-2022 time period, which contain all the information required in the research variables; (3) and companies that publish stock prices at the close of 2018-2022. This process resulted in 23 companies, and the final sample of observations obtained was 115 data points. The research results show that simultaneously, financial ratio variables and profit growth significantly influence stock prices. This means that the combination of these variables has a strong impact on company share price movements in the LQ-45 index. However, when analyzed partially, only the Earning Per Share (EPS) variable has a significant influence on stock prices. This shows that EPS has a more dominant role than other variables in influencing company stock prices in the LQ-45 index.